Synthetics, mineral oils, and bio-based lubricants : chemistry and technology - Rudnick, Leslie R., 1947- (Boca Raton : CRC Press, 2013)
'Preface Synthetic fluids and bio-based lubricants continue to grow. The global synthetic lubricant market is expected to grow to over 12% before the end of this decade. The European region is the largest consumer of synthetics followed by North America and then Asia-Pacific. Changes in North America are expected to improve demand for synthetic oils, with Honda and Toyota recommending 0W multigrade passenger car engine oils, and many high-performance sports cars are delivered with full synthetic motor oils as factory fill. Global industrial synthetic and semisynthetic use continues to grow driven by modern equipment, advanced technology, and government regulations. Synthetics are now required in many applications due to severe operating conditions or corrosive environments. In the area of bio-based lubricants, there have been advances in the stability of the oils that are now available in industrial useful quantity. Bio-based lubricants are an attractive alternative to petroleum-based lubricants in certain applications. Increased use of bio-based lubricants is also being driven by new government regulations. Chemical companies are also looking at approaches to non-petroleum-based lubricant base oils. For example, DuPont has bioengineered soybean seeds to yield soybean oil that is more stable to oxidation. Various chemical reactions have been used to reduce the pour point of vegetable oils, and epoxidation is also used to improve oxidative stability. Recently, Albemarle announced a partnership with Amyris to produce a new base fluid based on farnesene. Another area expected to compete will be the gas-to-liquids base oils from Shell-Qater Petroleum's Pearl Plant. The plant is expected to produce 4 and 8 cSt Group III and a 3cSt Group II'--
Book is accompanied by 1CD entitled' Synthetics, mineral oils, and bio-based lubricants: chemistry and technology.' bearing same call number and available at PL2.
Includes bibliographical references and index.
Keywords: Lubrication and lubricants